Studi Interaksi Segmen Dimer Kitosan...Nikotinamida secara Komputasi Ab Initio dan Eksperimen - Wibowo, Sapto Adi (Chem Info Journal, 2013)
The research has been done on theoritical study interaction between segment chitosan dimer and nicotinamide by ab initio computational dand experimental. The aims of this research is to determine interaction energy between segment chitosan dimer and nicotinamide in specific configuration by ab initio computational method and determine encapsulation efficiency nicotinamide with variation nicotinamide concentration to rasio (b/v) chitosan with acetic acid (1%) 20mg/20mL. The method that used is ab initio quantum mechanical calculations at theoritical level and basis sets RHF/6-31G (d, p) and experiment with centrifugation method. The result of calculation showed interaction energy between dimer chitosan segment…nicotinamide on first configuration has interaction energy -65,254 kJ/mol or - 15,596 kkal/mol and second configuration has interaction energy -57,061 kJ/mol or -13,63791 kkal/mol. Encapsulation efficiency (EE) nicotinamide in range nicotinamide concentration variation 500 ppm – 2.500 ppm to rasio (b/v) chitosan with acetic acid (1%) 20mg/20mL average 46,83%. The difference of interaction energy between nicotinamide with the chitosan in configuration 1 and configuration 2 can explain the slow-release process of nicotinamide from the chitosan matrix. Interaction in configuration 2 easier released than configuration 1 at time release process.